3D Modeling and Mechanism Analysis of Breaking Wave-Induced Seabed Scour around Monopile. (17th March 2020) - Liu, Xiaojian; Liu, Cheng; Zhu, Xiaowei; He, Yong; Wang, Qisong; Wu, Zhiyuan
Abstract : Breaking wave-induced scour is recognized as one of the major causes of coastal erosion and offshore structure failure, which involves in the full 3D water-air-sand interaction, raising a great challenge for the numerical simulation. To better understand this process, a nonlinear 3D numerical model based on the open-source CFD platform OpenFOAM® was self-developed in this study. The Navier–Stokes equations were used to compute the two-phase incompressible flow, combining with the finite volume method (FVM) to discretize calculation domain, a modified VOF method to track the free surface, and a k − ε model to closure the turbulence. The nearshore sediment transport process is reproduced in view of shear stress, suspended load, and bed load, in which the terms of shear stress and suspended load were updated by introducing volume fraction. The seabed morphology is updated based on Exner equation and implemented by dynamic mesh technique. The mass conservative sand slide algorithm was employed to avoid the incredible vary of the bed mesh. Importantly, a two-way coupling method connecting the hydrodynamic module with the beach morphodynamic module is implemented at each computation step to ensure the fluid-sediment interaction. The capabilities of this model were calibrated by laboratory data from some published references, and the advantages/disadvantages, as well as proper recommendations, were introduced. Finally, nonbreaking- and breaking wave-induced scour around the monopile, as well as breaking wave-induced beach evolution, were reproduced and discussed. This study would be significantly helpful to understand and evaluate the nearshore sediment transport.